Fabrication and characterization of medium density fiber board prepared from enzyme treated fiber and lignin based bio adhesive - Mohammed, Nasir (2013)
The emission of formaldehyde vapours from the adhesives such as urea formaldehyde (UF) and phenol formaldehyde (PF) is a serious concern associated with the wood composite industry. In this research a sequential and systematic application of laccase enzyme was applied to modify the rubberwood (Hevea brasiliensis) fibers and prepared an improved medium density fiberboard (MDF) without synthetic adhesive. The treated fiber was dried in an oven and stored in a desiccator whereas the solution obtained was called enzyme hydrolysis lignin (EHL) retained and concentrated until 3% solid content. The fiber properties were characterised by furrier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), thermo-gravimetric analysis (TGA) and x-ray diffrection (XRD). However the EHL and concentrated EHL were characterised by Brookfield viscometer, FTIR, DSC and TGA. Laccase treatment to fiber was optimised in order to obtain the best and improved fiber for MDF manufacturing. The best reaction parameters such as temperature, time, pH and enzyme amount, were investigated using response surface methodology. Crystallinity index was taken as response and maximum up to 10% increment was observed. The first approach included the laccase treatment to wood fiber in various amounts and reaction time in the pulp suspension. A successful binderless board were prepared from treated fibers at different platen temperature and at various pressing time. Water resistance properties and mechanical test such as MOE, MOR and IB of the boards were investigated. The binderless boards could not stand for longer time in water, whereas the mechanical properties were not strong enough to meet the international standard as per the ASTM D1037. Thus in order to improve the strength of MDF boards, another approach was applied and concentrated enzyme hydrolysis lignin (Con-EHL) was used as an adhesive. To evaluate the capability of Con-EHL as an adhesive, 6 mm MDF board of density 800 (±10) kg/m3 was prepared from 5, 10 and 15% con EHL by weight of fiber and it was compared with standard UF based boards prepared using the same parameters. The prepared MDF boards exhibited a higher mechanical strength and meet the international standard but the board still cannot stand in the moisture resistance test. In the third approach, nine different combinations of soy-lignin based adhesives were prepared using different parameters such as pH and soy content. Physical and chemical properties of soy-lignin adhesives were investigated. It was observed that the MDF prepared by the alkali treated soy-lignin adhesives have improved physical and mechanical properties. Water absorption and thickness swelling was reduced in comparison to previous boards. Mechanical properties were comparable to the commercial grade MDF boards. In the fourth approach, the alkali based soy-lignin was further improved by increasing the soy content up to 20%, and treating it with different chemicals to improve the water resistance. The physical and mechanical properties of MDF were compared with commercial grade UF based MDF. Mechanical properties were found comparable to UF based MDF whereas thickness swelling and water absorption was observed better than the “C-series” of soy lignin adhesive. The present soy lignin based adhesive can be used as a replacement for the formaldehyde based adhesive. It will be more ecofriendly and less harmful for the health